PENGETAHUAN DENGAN SIKAP WPS UNTUK TES HIV MELALUI KLINIK VCT - Sriwitati, Joce Desak Made; Rastiti Sumarasih, Ni Kadek (Jurnal Genta Kebidanan, 2017)
Abstract : Knowledge With Wps’s Attitude For Hiv Test Trough VCT Clinic. Purpose of this research is to find out the correlation of knowledge with Sex Worker Woman (WPS)’s attitude for HIV test trough VCT clinic at Local Government Clinic Working Area II of North Denpasar year 2016. The research type is analytic correlation with cross sectional approach, and purposive sampling technique with 55 respondents.  Data collection technique used questionnaire with Spearman’s Rho statistical test. Statistical test result shows that correlation coefficient between knowledge with attitude (rxy) is 0.404 at significance degree of 0.002.  Because that significance degree of p value < 0.05 and rxy (0.404) < rtabel  (0.261) then there is positive and significant correlation between knowledge of Sex Worker Woman (WPS) and attitude of Sex Worker Woman (WPS) for HIV test trough VCT clinic with correlation level of moderate.   Abstrak : Pengetahuan Dan Sikap WPS Terhadap Tes HIV Melalui Klinik VCT. Tujuan penelitian ini untuk mengetahui hubungan pengetahuan dengan sikap Wanita Pekerja Seks (WPS) untuk tes HIV melalui VCT di Wilayah Kerja Puskesmas II Denpasar Utara Tahun 2016. Jenis penelitian adalah analitik korelasi dengan pendekatan cross sectional, dan teknik purvosive sampling dengan 55 responden. Alat pengumpulan data menggunakan kuisioner dengan uji statistik Spearman’s Rho. Hasil uji statistik menunjukan koefisien korelasi antara pengetahuan dengan sikap (rxy) sebesar 0,404 pada derajat kemaknaan 0,002. Karena derajat kemaknaan p value < 0,05 dan rxy (0,404) < rtabel  (0,261)maka terdapat hubungan yang positif dan signifikan antara pengetahuan Wanita Pekerja Seks (WPS) dengan sikap Wanita Pekerja Seks (WPS) untuk tes HIV melalui klinik VCT dengan tingkat korelasi sedang.